Influence of Experience in Industrial Work Practices on Student Work Readiness Light Technology Vehicle Engineering at Indomobil Nissan Datsun East Java in 2019 - Handayani, Novi; Susila, Wayan; Wailanduw, Grummy (International Journal for Educational and Vocational Studies, 2019)
Based on BPS in 2019, the highest middle class unemployment force is for SMK graduates, which is 11.24% of the total 7 million people. Based on this, it can be seen that the purpose and function of this vocational high school is not yet well underway, because with a ratio of 51% of Vocational High Schools and 49% of the total number of students absorbed by the industrial world to SMK graduates, only 35% while high school graduates 65%. This study aims to find a correlation between industry work practice experience on work readiness research was an ex post facto study. The study population consisted of TKR students who were carrying out industrial work practices in the official workshop of Indomobil Nissan Datsun in East Java in 2019. Data collection techniques were in the form of questionnaires for industrial work experience experience variables (X₁), work interest (X₂) and self-confidence (X₃), and for the work readiness variable there are three domains, cognitive and psychomotor domains, data collection in the form of tests, and affective domain variables in the form of observation. Data analysis of this study using multiple regression and assisted using SPSS for Windows. The results of this study are expected to There is a positive correlation between apprenticeship experience on work readiness (sig. Cognitive domain value of 0.001; sig. Affective domain value of 0.031; and psychomotor domain sig value of 0.004) in TKR students who are implementing apprenticeship in Indomobil's official workshop Nissan Datsun in East Java in 2019.